Human β‐defensin 3 induces STAT1 phosphorylation, tyrosine phosphatase activity, and cytokine synthesis in T cells. Issue 3 (26th June 2013) - Meisch, Jeffrey P.; Vogel, Ryan M.; Schlatzer, Daniela M.; Li, Xiaolin; Chance, Mark R.; Levine, Alan D.
Abstract : In T cells, human β‐defensin 3 induces STAT1 tyrosine phosphorylation, tyrosine phosphatase activity, and SHP‐2 nuclear accumulation, which inhibits IFN‐γ signaling and enhances cytokine production. Abstract : The AMP hBD‐3 stimulates numerous immune effector functions in myeloid cells and keratinocytes, predominantly through the MAPK signaling cascade. In contrast, hBD‐3 was reported to neutralize the activation of T cells by antagonizing MAPK signaling initiated by SDF‐1α through CXCR4. With the use of complementary proteomic and immunochemical approaches, we investigated possible stimulatory effects of hBD‐3 on T cells and demonstrate that hBD‐3 induces STAT1 tyrosine phosphorylation within 5 min yet is unable to induce MAPK activation. Inclusion of a PTPase inhibitor increased hBD‐3‐induced phosphorylation dramatically, suggesting that hBD‐3 also stimulates PTPase activity concurrently. The increase in PTPase activity was confirmed by demonstrating that hBD‐3 suppresses IFN‐γ‐induced STAT1 tyrosine phosphorylation but not STAT1 serine and ERK1/2 threonine phosphorylation and stimulates the translocation of SHP‐2 into the nucleus within 15 min. The signaling pathways initiated by hBD‐3 may lead to the observed enhancement of distinct T cell effector functions during TCR activation, such as the increase in IL‐2 and IL‐10, but not IFN‐γ secretion. Thus, hBD‐3 initiates distinct lineage‐specific signaling cascades in various cells involved in host defense and induces a concurrent tyrosine kinase and tyrosine phosphatase signaling cascade that may activate simultaneously the targeted T cells and inhibit their response to other immune mediators. Furthermore, these results suggest that this evolutionarily conserved peptide, which exhibits a broad spectrum of antimicrobial and immunomodulatory activities, serves to integrate innate and adaptive immunity.